Problems of Implementing Cyber Notary in Notarial Deeds in Indonesia - Jamus, Mohammad; Budi, Grimaldi Setia; Sari, Dian Rosita; Parmitasari, Indah (Sultan Agung Notary Law Review, 2024)
This article reviews the implementation of Cyber Notary in Indonesia. Cyber Notary is a concept that integrates the authority of a Notary with information technology. The use of technology in notarial services in Indonesia has not been optimized. Article 15 paragraph (3) of Law Number 2 of 2014, which amends Law Number 30 of 2004 concerning the Position of Notary, stipulates that Cyber Notary only applies to the certification of transactions between a notary and the relevant party, without covering the authority of a Notary as a whole. A Notary is a public official who has a role in carrying out legal acts in accordance with Law Number 2 of 2014 concerning the Position of Notary. Notaries adapt and follow the changing times to carry out their positions, the goal is for Notaries to be able and able to face global challenges and competition. Cyber Notary can facilitate and accelerate the performance of Notaries in the future. The use of an electronic digital system in Cyber Notary is expected to make better and more effective changes in the world of Notaries. Regarding the authority of Notaries to make deeds electronically, it is clearly an obstacle for Notaries. Despite its problems, Cyber Notary certainly has opportunities that can be used in Indonesia. To improve the quality of public services with technology in the notary field effectively and better, rapid improvements in the quality of technology are needed in this digital era. Therefore, the author recommends the adoption of the Cyber Notary concept in changing notary law. However, Indonesia has not been able to fully adopt this concept due to differences in authority and verification systems between common law countries and civil law systems in Indonesia. In addition, effective regulatory changes are needed in the process of changing notary law because there are still many regulations governing the authority of Notaries.